(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
HRD practices change the capabilities of employees at all levels in an organization and in this way assume a significant role in driving advancement and development. Individuals’ capabilities and how those capabilities are utilized within the organization due to advancements in the systems and processes of HR management involving HRD helps to leverage the many-fold benefits. In that trio of extraordinary capacities, HRD centers focus on learning and improvement at the individual, group, and organizational levels that happens when employees have the knowledge, competencies, skills, and attitude for getting the hang of, facing attentive challenges, sharing information, and thinking imaginatively, and when organizations offer help by managing it through effective KM[1]. Ishak et al. (2010) propose KM is fundamental for building up the human asset. It is additionally recommended that HRD is fundamental for developing the knowledge that flows through the KM framework. Hence, the purpose of this study is to investigate the pathways leading from HRD to OP through KM as a mediator and presenting a comprehensive framework for steel companies of India to strategize effective HRD practices for better and effective KM for enhanced Perf organization-wide. The main objective of this topic is to measure the effect of HRD Practice, Knowledge Management on the real organizational performance in the steel Industries in India. In this study, we have used SEM for the measure of the mediating effect of knowledge Management on HRD Practices for organizational performance. [1] https://www.intechopen.com/books/knowledge-management-strategies-and-applications/knowledge-sharing-and-human-resource-development-in-innovative-organizations#B3